THE LIFE OF ABU RAYHAN BERUNIY, THE GREATEST SCIENTIST IN ASIA - Sherova Gulasal Sadilloyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: Abu Rayhan Muhammad ibn Ahmad al-Biruni was an encyclopedist of the medieval East. He was the first in the Middle East to say that the Earth can revolve around the Sun and determine the size of the Earth's circumference. Little is known about Beruni's early life, only that he was an orphan. Ma'mun was a scientist of the Muslim East who lived in 1035-1036 and wrote more than 160 works. Beruni conducted observations and experiments on rare metals and precious stones for several years, and later, based on these studies.